Amnestic Mild Cognitive Impairment Is Associated With Frequency-Specific Brain Network Alterations in Temporal Poles - Jacini, Francesca; Sorrentino, Pierpaolo; Lardone, Anna; Rucco, Rosaria; Baselice, Fabio; Cavaliere, Carlo; Aiello, Marco; Orsini, Mario; Iavarone, Alessandro; Manzo, Valentino; Carotenuto, Anna; Granata, Carmine; et al. (Frontiers in Aging Neuroscience, 2018)
There is general agreement that the neuropathological processes leading to Alzheimer’s disease (AD) begin decades before the clinical onset. In order to detect early topological changes, we applied functional connectivity and network analysis to magnetoencephalographic (MEG) data obtained from sixteen patients with amnestic Mild Cognitive Impairment (aMCI), a prodromal stage of AD, and sixteen matched healthy controls. Significant differences between the two groups were found in the theta band, which is associated with memory processes, in both temporal poles (TPs). In aMCI, the degree and betweenness centrality (BC) were lower in the left superior TP, whereas in the right middle TP the BC was higher. A statistically significant negative linear correlation was found between the BC of the left superior TP and a delayed recall score, a sensitive marker of the “hippocampal memory” deficit of early AD. Our results suggest that the TPs, which are involved early in AD pathology and belong to the memory circuitry, have an altered role in the functional network in aMCI.